The Effect of Foster Care and Self-Efficacy on the Physical Activities of Elementary School Students - Samsudin Samsudin; Ali Maksum; Anung Priambodo (BIRCU, 2021)
Parenting is a process of interaction between parents and children in educating, guiding, and directing the development of children's personalities. Parenting patterns play an important role in the formation of children's self-efficacy to behave independently and always strive in the face of every difficulty. This study aims to examine the influence of foster care patterns and self-efficacy on physical activity. The subject of this study was grade 6 students of SD Islam Raden Paku Surabaya as many as 70 students consisting of 40 male students and 30 female students. The data was collected using questionnaires and analyzed using multiple regressions. The results showed that the pattern of foster care and self-efficacy together significantly influenced the physical activity of elementary school students in grade VI, with a score of F of 3,765 at a significance of 0.005. Authoritarian parenting patterns significantly influenced the physical activity of students with a beta score of 0.259 at a significance of 0.027, while the other three foster patterns had no significant effect. Self-efficacy significantly influenced the physical activity of students with a beta score of 0.458 at a significance of 0.001.